Parents' willingness to vaccinate their child against COVID 19: A cross sectional study - Sowmya SG; Shreya Adavalath; K. Shreedhara Avabratha (Al Ameen Medical College, 2024)
Background: An effective COVID vaccine in children will decrease the severity of illness in children as well as transmission rates of the virus, thereby providing direct and indirect benefits. The Government of India has decided to extend the COVID-19 vaccination program to children between 2-18 years of age. In such a situation, parents have the right to decide whether or not to vaccinate their child. Methods: This was cross sectional questionnaire based study conducted on parents of children under 18 years attending outpatient department in tertiary hospital, Mangalore. Data was collected using pretested semi structured questionnaires which included sociodemographic factors and reasons for willingness or unwillingness. Data was analysed using descriptive statistics, chi square test and outcomes expressed as frequency, proportions and percentages. Results: In our study, it was found that a majority of parents (84.5%) were willing to vaccinate their child against COVID 19. The reason for willingness was that they felt vaccination is necessary to control the pandemic (70.7%).15.5 % of the parents were not willing to vaccinate their child. Majority of the parents (70.5%) had concerns regarding the safety profile of the vaccine. The study did not find any significant relationship between the age, gender, socioeconomic status or education of the parents with their willingness to vaccinate their child. Conclusion: Majority of the parents in our study were willing to vaccinate their children against COVID 19 and appropriate strategies need to be initiated to increase the vaccination rates among children.